The relationship between self-esteem and achievement motivation among successful and unsuccessful athletes in east Azarbaijan province - Behnam Maleki; Hassan Mohammadzadeh; MirHassan SeyedAmeri; SeyedHojjat Zamani Sani (Vesnu Publications, 2011)
Introduction: The aim of this study was to investigate the relationship between self-esteem and achievement motivation among successful and unsuccessful athletes in West Azerbaijan Province. Methods: Two-hundred athletes were divided into two groups of successful athletes (n=100, 50 males and 50 females) and unsuccessful athletes (n=100, 50 males and 50 females) while the term «successful» means that the subject has win medals at national and international official competitions and «unsuccessful» means he/she has not been able to do so. Gill and Deter's sport orientation scale (SOQ) (1998) and revised self-esteem questionnaire (Cupper-Smith, 1968) were the assessment instruments used in this study. Pearson Correlation and t-test (α<0.05) were applied for the statistical analysis of data. Results: The results showed that there is a significant correlation between self-esteem and achievement motivation in both studied groups. Moreover, successful and unsuccessful athletes significantly differed in terms of self-esteem and achievement motivation so that self-esteem and achievement motivation were significantly higher in successful athletes compared to unsuccessful athletes. Conclusion: It seems that athletes' beliefs interfere with their performance. Therefore equal attention must be paid to fitness and sport skills and motivational variables through appropriate physical education and providing conditions in which athletes feel competence and motivation and experience success. Coaches are advised to provide timely feedback, necessary support and constructive criticism in order to give their students the opportunity to be aware of their capabilities and increase their achievement motivation accordingly.  Keywords: self-esteem, achievement motivation, successful athletes, unsuccessful athletes